Species composition, abundance and distribution of phytoplankton in surface waters of Taklong Island, Nueva Valencia, Guimaras. - Sorongon, Reynaldo S. (1994.)
An exploratory study of the composition, abundance, diversity and similarity of surface phytoplankton at three stations (Talisay, Balas-Balabag and U.P. Channel) in Taklong Island, Nueva Valencia, Guimaras was conducted. Some physico-chemical parameters, for example, temperature, salinity, pH, phosphorus and total nitrogen concentration were monitored together with plankton tows., Fifty-seven species belonging to 2 phyla, 2 classess, 3 orders, 15 families and 27 genera were recorded. The predominant phytoplankton during the study were the diatoms. Dinoflagellates were represented in fewer number. The most abundant species was Rhizosolenia styliformis followed by Thalassiosira subtilis and then Bacteriastrum hyalinum. Highest species diversity was observed during the twelve noon sampling while lowest diversity was during the twelve midnight sampling in all three stations. Station III (U.P. Channel) had the highest diversity in all sampling times while station I (Talisay) had the lowest diversity in all sampling times. It was stations II and III during the six PM sampling which showed highest similarity index. Highest similarity index was also revealed during six PM and twelve PM samplings at station III. Nonparametric Randomized Block ANOVA and then multiple comparisons for nonparametric randomized block ANOVA showed significant difference (p<0.05) in index of diversity between stations I and III. Among the physico-chemical parameters monitored only temperature is significantly correlated with index of diversity (p<0.05).
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Waters -- Taklong Island,Nueva Valencia, Guimaras